2010
DOI: 10.1016/j.cardfail.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations From Implantable Defibrillators to Prevent Death in Heart Failure

Abstract: Background Indications for implantable cardioverter-defibrillators (ICDs) in heart failure (HF) are expanding and may include more than 1 million patients. This study examined patient expectations from ICDs for primary prevention of sudden death in HF. Methods and Results Study participants (n = 105) had an EF <35% and symptomatic HF, without history of ventricular tachycardia/fibrillation or syncope. Subjects completed a written survey about perceived ICD benefits, survival expectations, and circumstances u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 51 publications
(46 reference statements)
7
106
1
7
Order By: Relevance
“…In fact, a number of complications related to implantation and device activation have been described with the use of both devices. [7,31] Major complications include inappropriate shocks, device infection, lead malfunction and complications related to extraction of devices. [25] A harmful effect related to CRT has been found in patients with a QRS duration < 130 msec.…”
Section: Crtmentioning
confidence: 99%
“…In fact, a number of complications related to implantation and device activation have been described with the use of both devices. [7,31] Major complications include inappropriate shocks, device infection, lead malfunction and complications related to extraction of devices. [25] A harmful effect related to CRT has been found in patients with a QRS duration < 130 msec.…”
Section: Crtmentioning
confidence: 99%
“…5 It is unclear how possible benefits and harms are communicated to patients during the clinical encounter and how patients make sense of this information. Indeed, data on patients' expectations of ICDs suggest that survival benefits might be substantially overestimated, 21 and improvements to how information on the clinical rationale for ICDs (including the fact that simple ICDs do not confer any symptom or quality-of-life benefits) is communicated to patients and their relatives may be warranted. It has been shown that patients eligible for different therapies might not be fully aware of the benefits and harms of each option, 15,16 and the psychosocial impacts of available treatment or management options rarely feature in risk communication.…”
Section: Structure Of the Reportmentioning
confidence: 99%
“…The patient's wishes for his or her ICD should be addressed as part of the routine discussion of goals of care and resuscitation status. Many will choose to keep the device active 167,[171][172][173][174] ; however, it is appropriate to identify a future time when deactivation would be desired. Staff should identify the cardiology team managing the device.…”
Section: Management Of Cardiac Implantable Electronic Devices In Hf Pmentioning
confidence: 99%